Analyzing and modeling public interest in fishery resources: Proposing flagship species for promoting sustainable fisheries in Japan - Shun Ota; Ken-ichi Hayashizaki (PLoS ONE, 2026)
Effective management of natural resources fundamentally relies on public support, making an understanding of the dynamics of public interest crucial for successful conservation policy. Globally, fisheries face sustainability challenges, yet public engagement often remains a key barrier to effective policy implementation. While public interest has traditionally been assessed through surveys, which are often costly and lack real-time granularity, digital trace data such as search engine queries offer a high-frequency alternative to monitor public attention. However, the primary drivers shaping public interest in specific fishery resources, and how these insights can be leveraged to select effective conservation symbols, remain poorly understood. Here we show, using Google Trends data for key Japanese fishery resources, that public interest is driven by two distinct archetypes—predictable seasonality and regional supply—and identify Pacific saury ( Cololabis saira ) as a unique species whose public profile is increasingly linked to its declining stock status. While previous assumptions might link consumer interest primarily to price and seasonal availability, our analysis reveals that for most species, market prices are a stronger driver than catch volumes. Crucially, Pacific saury diverges from this pattern; its public salience is uniquely influenced by both catch volume and a growing awareness of its resource depletion, making its profile more complex than that of a simple commodity. These findings demonstrate that the flagship species concept, traditionally applied to terrestrial megafauna, can be empirically adapted to exploited marine resources, providing a data-driven framework for selecting species that act as effective anchors for conservation messaging. Our methodology offers a low-cost, transferable workflow for integrating social data into resource management, a critical step for bridging the science-policy-society gap. By transforming passive digital footprints into actionable insights, this approach empowers conservation efforts to become more dynamic and responsive to public sentiment, ultimately fostering greater societal engagement in sustainability.